Perancangan Pondok Pesantren Dengan Pendekatan Arsitektur Tropis Di KUnciran Jaya, Kecamatan Pinang, Kota Tangerang, Banten - Bagas Bagas; Tri Endangsih; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Islamic boarding schools are a means of non-formal Islamic education that play a role in advancing the life of the nation as well as being a place to explore religious sciences, especially Islam, which is the majority in Indonesia. Islamic boarding school education is education that prioritizes Islam as a guideline. The purpose of this research is to realize the concept of planning and designing Islamic boarding schools in Tangerang City with the theme of Tropical Architecture which seeks to change the behavior patterns of its inhabitants to protect the surrounding environment from damage and better sustainability in the future. Analytical descriptive method for architectural design approach is carried out with an understanding of the principles of tropical architectural design, besides that, the activity group approach, capacity approach and space size are carried out. By applying the concept of tropical architecture can create a good learning environment and can prevent global warming problems. Building materials and components that have sustainable criteria to support the application of tropical architecture can be applied to buildings that function as a forum for santri activities in Islamic boarding schools.